1200V 4H-SiC trench MOSFET with superior figure of merit and suppressed quasi-saturation effect. (August 2021) - Fu, Hao; Wei, Zhaoxiang; Liu, Siyang; Wei, Jiaxing; Xu, Hang; Ni, Lihua; Yang, Zhuo; Sun, Weifeng
Abstract: A superior figure-of-merit (FoM) 1200 V class 4H-SiC trench MOSFET with p + shielding region partially surrounded by the buried n region is proposed in this paper. The buried n region is introduced to restrain the lateral extension of the depletion layer formed by p + shielding region at the quasi-saturation (QS) state, which leads to a significant improvement of the transfer and forward characteristics. The buried n region expands the current path in the JFET region, decreasing the JFET resistance and improving the maximum transconductance (gfs ). Thereby the QS effect of the device with p + shielding region caused by the JFET region gets effectively suppressed. Moreover, the influences of the parameters of the buried n region on the breakdown voltage (BV), the dynamic characteristic and the gate oxide reliability are investigated to determine the optimized device cell structure. Simulation results show that the specific on-resistance (Ron, sp ) of the proposed device with the optimized buried n region is decreased by 19.3%, reaching a value of 1.63 mΩcm 2 . The maximum gfs is enhanced by 30%. The FoM1 (FoM1  = BV 2 /Ron, sp ) is utilized to judge the trade-off relationship between the BV and the Ron, sp, which is improved by 20.5%, reaching 1.45 kV 2 /mΩcm 2 . Highlights: The mechanism of the quasi-saturation effect for the 4H-SiC trench MOSFET with p+ shielding region is investigated. An improved 1200 V 4H-SiC trench MOSFET with p+ shielding region partially surrounded by the buried n region is proposed. The JFET current path maintains open and can not be controlled by the gate bias at the quasi-saturation state.